A global analysis of urbanization effects on amphibian richness: Patterns and drivers. (March 2022) - Yang, Lu; Zhao, Shuqing; Liu, Shuguang
Highlights: We empirically generalized the urbanizational gradients of amphibian richness globally. We proposed that urbanizational diversity gradient (UDG) should be recognized as another general principle. We also proposed the heat-and-threat balance (HATB) hypothesis to explain UDG. Abstract: Urbanization presents an unplanned and highly replicated global experiment to understand biotic responses to global changes. Here we conducted a global analysis on patterns and drivers of urbanization effects on biodiversity using the global amphibian richness dataset along with background climate and the continuous rural-urban gradients. We, for the first time, empirically generalized the urbanizational gradients of amphibian richness at the global scale and in different climate zones despite the substantial differences in history, ecological context, and socioeconomic conditions across large geospatial extents. We found a positive imprint of urbanization on amphibian richness in cool and climate zones whereas the presence of urban thermal stress in high temperature climate zones. Anthropogenic forces behind the urbanization gradients entangled with environmental variables directly and indirectly drove the patterns as revealed by the structural equation modeling (SEM). The urbanizational diversity gradient (UDG) found in this study might signify the existence of another general principle in ecology analogous to well-known latitudinal and elevational diversity gradients. We proposed the heat-and-threat balance (HATB) hypothesis to explain UDG: urbanization-induced heat would promote biodiversity if the ambient temperatures are cooler than their optima. Alternatively, it may put threats on biodiversity when the ambient temperatures are close to their optima. There is an urgent need to advance the knowledge on UDG in an urbanizing planet by additional studies from diverse taxa, various geographical locations, and at different scales.